Silica gel supported bis-cinchona alkaloid: A highly efficient chiral ligand for heterogeneous asymmetric dihydroxylation of olefins - Song, CE; Yang, JW; Ha, HJ (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
Comparable reactivity and enantioselectivity to those in homogeneous solution have been achieved in heterogeneous catalytic asymmetric dihydroxylation (AD) of olefins using a new silica gel supported cinchona alkaloid containing 1,4-bis(9-O-quininyl)phthalazine ((QN)(2)-PHAL). Moreover, the silica supported alkaloid exhibited much greater binding ability for OsO4 than its homogeneous analogue. (C) 1997 Elsevier Science Ltd.
Keywords: STATIONARY PHASES; CATALYTIC DIHYDROXYLATION; POLYMER SUPPORT; ALKENES; DERIVATIVES; RESOLUTION